Archimancy - White, J. A (White, J. A. Shadow school, 2019)
Cordelia Liu knew Shadow School was going to be different. Still, she didn't expect the school grounds to be filled with ghosts. Cordelia soon realizes she's not the only one who can see the ghosts; her new friend Benji can too. Together with super-smart Agnes, the trio are determined to find out why the ghosts are there, and whether there's a way to set them free. But the school was created with more sinister intentions, and someone is willing to go to extreme lengths to ensure that the ghosts remain trapped forever